Linguistic game plays (version for Hindi) - Gazieva, Indira A.; Zakharova, Anna; Isaeva, Ksenia (Investigationes Linguisticae, 2010)
This article describes how teachers of Hindi language can diversify their lessons teaching language for one or twoyear students. The research concerns the usage of linguistic game Sudoku on Hindi lessons. The article from which we have made a start is called “Learning to Hypothesize with Confidence through Sudoku Game Play”. It was written by Y.L.Teresa Ting, a teacher of the University of Calabria (Italy). The Hindi version of this game aims to stimulate interest among students in the study of complex grammar of Hindi language, especially mastering the skills for using postpositions, which are not in their native language. This game is suitable both for self-study student, and to conduct a linguistic group.